Rudolph the red-nosed reindeer [videorecording (DVD)] - Roemer, Larry; May, Robert L. (Robert Lewis), 1905-1976; Ives, Burl, 1909-1995; Richards, Billie ([Publisher not identified], 2014)
Relive the magic when Rudolph visits the Island of Misfit Toys, and Santa asks Rudolph to guide his sleigh on Christmas Eve.